The Effectiveness of Collaborative Writing Strategy in Improving Essay Writing Skills of University Students in the EFL Context - La Ode Nggawu; Desy Liliani Husain; Sitti Agustina; Yustih Yasin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Essay writing skills are able to predict a person's success in higher education because the processes involved when composing it are indeed able to hone the abilities or skills of a student in academic life. This study aims to improve the essay writing skills of English Education students by applying the collaborative writing strategy. Classroom Action Research design is applied to answer the research questions, and then there are two cycles conducted successfully in the research. Each cycle consists of several stages, namely planning, implementation, observation, and evaluation, divided into three meetings. The research data were collected by assessing students’ writing in each cycle and analyzed using the band score from NCTE. The study results indicate an increase in the quality of students' essay writing skills after doing the writing process through Collaborative Writing in several aspects of writing. The effectiveness of this strategy was seen that more than 75% of students involved got their writing scores improved. It proves that the fruitful collaboration and interaction among students in collaborative work enhances the quality of writing, making it better and worth reading.